Effects and clinical application of cannabinoids for the treatment of periodontal disease: a systematic review - Laura García-Gutiérrez; Yuliana Hoyos-Castrillón; Sara Garcés-Londoño; Sandra Jaimes-Ríos (Universidad de Antioquia, 2024)
Introduction: cannabinoids have a wide range of biological effects and are currently used for therapeutic purposes in modern medicine. The objective was to determine the effects and clinical application of cannabinoids as a therapeutic alternative for periodontal disease. Methods: we conducted a systematic review following the Cochrane manual for systematic reviews' recommendations to address the following inquiries: 1) What is the impact of non-surgical therapy with cannabidiol compared to conventional non-surgical therapy on the level of insertion in patients with periodontal disease? 2) What are the potential biological and microbiological effects of cannabinoids in the treatment of periodontal disease? The primary outcome was changes in the periodontal attachment level (CAL) and secondary outcomes included changes in probing depth (PD), changes in bleeding on probing (BoP), report of adverse effects and microbiological and biological effects. Results: out of 59 potential studies, 26 were excluded in the initial screening, and 33 full-text studies underwent further review. Among these, 13 were excluded for not meeting the selection criteria, resulting in 20 studies included in the qualitative synthesis. Notably, only one highly biased human clinical study was identified. In vitro and animal studies demonstrated that cannabinoids possess bactericidal properties, anti-inflammatory potential, and modulating activity on periodontal bone resorption. Conclusions: the available scientific evidence is scarce to recommend the use of cannabis derivatives for the treatment of periodontal disease. Despite promising findings in preclinical studies indicating therapeutic potential, further investigation is required to assess its application in human subjects.